Some Observations on the Problem of Marine Timber Destroying Organisms of Indian Coasts - Nair, N Balakrishnan (Fishery Technology, 1964)
In India the chief marine timber boring organisms are 2 species of Martesia, 28 species of shipworms, 4 species and a variety of Sphaeroma and 9 species of Limnoria besides bacteria and fungi. The occurrence, abundance and activity of the various species of borers show remarkable variations and fluctuations in the different harbours of India, each harbour or area having its own dominant set of species and an assemblage of less important forms, These species have their own characterestic preferences, life history and seasons of attachment and a scheme evolved for one locality may prove ineffective for another. Through a delicate and complex ecological adjustment the borers occurring in a locality have reached an interrelationship reducing interspecific and intraspecific competition. The seasons of settlement of the dominant borers in the different harbours of India are indicated. The need for a detailed biological enquiry is stressed.